Mimosine Toxicity in Leucaena Biomass: A Hurdle Impeding Maximum use for Bioproducts and Bioenergy - Ramli, N.; Jamaludin, A.A.; Ilham, Zul (Juniper Publishers, 2017)
Leucaena biomass could serve as a new commodity for bio energy production. It is well established as a feedstock for animal husbandry, due to its nutrient content and lower cost. However, the existence of mimosine caused loss of hair among ruminants. This paper provides a short review of current uses of Leucaena, from agriculture to bio energy. In the next section, the techniques to remove Leucaena toxicity caused by the toxic non-protein amino acid mimosine will be discussed. A common mimosine inactivation technique adopted for animal rations is dosage-dependent on the Leucaena portion and inclusion of iodine, iron, copper or sulphate in the diet. However, this technique is inefficient. Other approaches such as enzymes from ruminal microbes or soil bacteria and low-mimosine Leucaena clones have become new strategies to overcome this problem, although the toxicity is reduced it still can be seen. Future research is needed to if possible fully eliminate the toxicity and realize the goal of Leucaena utilization to produce both bio products and bio energy.